NKAP Regulates Senescence and Cell Death Pathways in Hematopoietic Progenitors - Shapiro, Michael Jeremy; Anderson, Joshua; Lehrke, Michael Jonathan; Chen, Meibo; Nelson Holte, Molly; Shapiro, Virginia Smith (Frontiers in Cell and Developmental Biology, 2019)
NKAP is a multi-functional nuclear protein that has been shown to be essential for hematopoiesis. Deletion of NKAP in hematopoietic stem cells was previously found to result in rapid lethality and hematopoietic failure. NKAP deficient cells also exhibited diminished proliferation and increased expression of the cyclin dependent kinase inhibitors (CDKIs) p19 Ink4d and p21 Cip1. To determine how dysregulation of CDKII expression contributes to the effects of NKAP deficiency, NKAP was deleted in mice also deficient in p19 Ink4d or p21 Cip1 using poly-IC treatment to induce Mx1-cre. Hematopoietic failure and lethality were not prevented by deficiency in either CDKI when NKAP was deleted. Inducible deletion of NKAP in cultured hematopoietic progenitors ex vivo resulted in a senescent phenotype and altered expression of numerous cell cycle regulators including the CDKI p16 INK4a. Interestingly, while combined deficiency in p16 INK4a and p21 Cip1 did not reverse the effect of NKAP deficiency on hematopoiesis in vivo, it did shift the consequence of NKAP deficiency from senescence to apoptosis in ex vivo cultures. These results suggest that NKAP may limit cellular stress that can trigger cell cycle withdrawal or cell death, a role critical for the maintenance of a viable pool of hematopoietic progenitors.